Overexpression of a SOC1-Related Gene Promotes Bud Break in Ecodormant Poplars - Gómez-Soto, Daniela; Ramos-Sánchez, José M.; Alique, Daniel; Conde, Daniel; Triozzi, Paolo M.; Perales, Mariano; Allona, Isabel (Frontiers in Plant Science, 2021)
Perennial species in the boreal and temperate regions are subject to extreme annual variations in light and temperature. They precisely adapt to seasonal changes by synchronizing cycles of growth and dormancy with external cues. Annual dormancy–growth transitions and flowering involve factors that integrate environmental and endogenous signals. MADS-box transcription factors have been extensively described in the regulation of Arabidopsis flowering. However, their participation in annual dormancy–growth transitions in trees is minimal. In this study, we investigate the function of MADS12, a Populus tremula × alba SUPPRESSOR OF CONSTANS OVEREXPRESSION 1 (SOC1)-related gene. Our gene expression analysis reveals that MADS12 displays lower mRNA levels during the winter than during early spring and mid-spring. Moreover, MADS12 activation depends on the fulfillment of the chilling requirement. Hybrid poplars overexpressing MADS12 show no differences in growth cessation and bud set, while ecodormant plants display an early bud break, indicating that MADS12 overexpression promotes bud growth reactivation. Comparative expression analysis of available bud break-promoting genes reveals that MADS12 overexpression downregulates the GIBBERELLINS 2 OXIDASE 4 (GA2ox4), a gene involved in gibberellin catabolism. Moreover, the mid-winter to mid-spring RNAseq profiling indicates that MADS12 and GA2ox4 show antagonistic expression during bud dormancy release. Our results support MADS12 participation in the reactivation of shoot meristem growth during ecodormancy and link MADS12 activation and GA2ox4 downregulation within the temporal events that lead to poplar bud break.